Elevated body mass index as a risk factor for chronic kidney disease: current perspectives - Garl (Dove Medical Press, 2014)
Jocelyn S Garland Department of Medicine, Queen's University, Kingston, ON, Canada Abstract: Chronic kidney disease (CKD) is defined by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative as the presence of reduced kidney function or kidney damage for a period of 3 months or greater. Obesity is considered a risk factor for CKD development, but its precise role in contributing to CKD and end stage kidney disease is not fully elucidated. In this narrative review, the objectives are to describe the pathogenesis of CKD in obesity, including the impact of altered adipokine secretion in obesity and CKD, and to provide an overview of the clinical studies assessing the risk of obesity and CKD development. Keywords: obesity, chronic renal disease, adipokine